Principles of Justice for Compensation for Land Procurement in Tamansari 11 Bandung City - Ali Said Hilabi; Mutiara Azura Mulyawan; Yuli Indrawati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Land acquisition is an activity carried out by the government in providing land by providing appropriate and fair compensation to parties who Affected In land acquisition for development in the public interest, there are principles that must be met, one of which is the Principle of Justice, which is based on the explanation of Article 2 letter b of Law No. 2/2012 that the "principle of justice" is to provide a guarantee of proper compensation to the Entitled Party. in the Land Acquisition process so that they get the opportunity to be able to carry out a better life. The government needs to apply the principle of the principle of justice in the context of compensation to the community whose land is needed for the public interest. However, unfortunately it turns out that the compensation provided by the Government to the residents of Tamansari 11 is deemed unfair, which means the Government should be able to provide compensation that is much more appropriate, taking into account that they have lived in the area for more than 20 years and that is where they can also get compensation. income from the livelihood they have, for example trading, then making the house as a boarding house and so on. The problems that occur in compensation for land procurement in Tamansari 11, Bandung City are based on DPKP3 Decree Number 538.2/1325a/DPKP3/2017 and the principle of justice for compensation for land acquisition in Tamansari 11, Bandung City. To answer this research, the analytical methods used are normative and qualitative. The results of this study that the principle of justice against compensation for land acquisition in Tamansari 11 Bandung City has not been achieved where this occurs because the Bandung city government does not carry out land acquisition procedures, namely deliberation to determine compensation as based on Law Number 2 of 2012.